Topographic controls of water balance response to air temperature increase in permafrost-affected watersheds - Debolskiy, Matvey V.; Hock, Regine; Alexeev, Vladimir A.; Romanovsky, Vladimir E. (Frontiers in Earth Science, 2023)
Observed increases in runoff in permafrost regions have not only been associated with changes in air temperature and precipitation but also changes in hydrological pathways caused by permafrost thaw, however, the causes and detailed processes are still a matter of debate. In this study, we apply the physically-based hydrological model WaSIM to idealized small watersheds with permafrost to assess the response of total runoff and its components surface runoff, interflow, and baseflow to atmospheric warming. We use an idealized warming scenario defined by steady atmospheric warming (only in winter) over 100 years followed by 900 years of constant air temperatures leading to permafrost thaw. Sensitivity experiments include 12 watershed configurations with different assumptions on slope, profile curvature, and hydraulic conductivity. Results indicate that when subsurface conditions allow for faster lateral flow, at the end of the warming scenario the watersheds with steeper slopes or negative (convex) profile curvature, and thus larger unsaturated zones, experience delayed permafrost thaw due to decreased thermal conductivity and lower initial soil temperatures compared to watersheds with gentle slopes or positive (concave) curvature. However, in the long term, they exhibit a higher increase in annual runoff and baseflow (and subsequently winter runoff) than watersheds with lower hydraulic conductivity and/or more gentle terrain. Moreover, after the warming, for watersheds in which permeability at depth is lower than in near-surface soil, steeper slopes facilitate a significant reduction of the increase in baseflow (and winter runoff) and instead promote interflow generation compared to the watersheds with gentle slopes or lower near-surface permeability. For the watersheds with less permeable soil, a steeper slope facilitates a lesser decrease in interflow, and the increase in total runoff is delayed. In addition, water balance response to the warming has little sensitivity to profile curvature when hydraulic conductivity is low. On the other hand, in watersheds with high hydraulic conductivity, profile curvature can considerably alter water balance response to warming. Convex watersheds exhibit a larger (albeit delayed) increase in runoff and baseflow (and associated decrease in interflow generation) compared to those with zero or positive profile curvature.